Reconstructing the Paleo‐Ecological Diet of Snow Petrels (Pagodroma nivea) From Modern Samples and Fossil Deposits: Implications for Southern Ocean Paleoenvironmental Reconstructions. Issue 4 (19th April 2023) - Berg, S.; Emmerson, L.; Heim, C.; Buchta, E.; Fromm, T.; Glaser, B.; Hermichen, W.‐D.; Rethemeyer, J.; Southwell, C.; Wand, U.; Zech, M.; Melles, M.
Abstract: Snow petrels ( Pagodroma nivea ), which are endemic to the Antarctic region, produce proventricular stomach oil from ingested food for feeding purposes but also spit the oil in the immediate surrounds of the nests, where it forms encrustations over time (Antarctic mumiyo). These deposits provide a unique opportunity to understand the paleo‐ecological diet of snow petrels and because the seabirds forage in the ocean, they potentially provide an archive of past marine environmental conditions in the Southern Ocean. For validating methods for reconstructions we use compositional data obtained on modern stomach oils and DNA data from fecal samples of snow petrels. We find that the distribution of carboxylic acid compounds in modern stomach oils and in the fossil deposits are consistent with variable contributions of fish and krill, which are the main constituents of modern snow petrel diet, and allows inference of past changes in snow petrel diet from the fossil record. Analyses of mumiyo deposits from six regions in East Antarctica reveal systematic differences in the isotopic composition of organic matter (δ 13 C and δ 15 N) and carboxylic acid patterns. This may suggest regional and/or temporal variability in the composition of snow petrels diet, likely differing in response to the prevailing environmental conditions in the foraging range of the birds, such as sea‐ice variability, polynya activity and primary productivity. Our study provides confidence for using these approaches for broader scale paleo‐studies in the future and for an assessment of the temporal changes and regional variability in snow petrel diet. Plain Language Summary: To better understand interactions of biological and physical processes in Antarctic marine ecosystems, we investigate fossil deposits of stomach oil of snow petrels for their use as a geological archive for past environmental changes. The deposits form over time in the surroundings of the nesting cavities of snow petrels, which produce stomach oil from ingested food but also spit it at nest robbers. In fresh oil the lipid and isotopic composition can be traced back to the composition of snow petrel food, such as variable proportions of fish and krill. From comparing the lipid and δ 13 C‐isotopic composition of modern oil to fossil deposits we suggest it is possible to identify changes in the diet of snow petrels in the fossil record. Since the composition of the diet is closely linked to the prevailing environmental conditions in the marine foraging region of the birds, such as summer sea ice extent, this information can be used for paleoenvironmental reconstructions. Our study of deposits from widely separated regions in Antarctica shows that there are spatial and temporal differences in the composition of stomach oil deposits, likely related to the prevailing environmental conditions. This finding underpins the application of our approach. Key Points: Modern stomach oil and feces of snow petrels are used to validate paleo‐proxies for environmental reconstructions in East Antarctica Biomarkers and isotopic composition of fossil stomach oil deposits of snow petrels reflect past composition in diet Changes in the composition of the paleo‐ecological diet reflect variations of environmental conditions in the coastal Southern Ocean